City size, migration, and urban inequality in the People's Republic of China - Binkai Chen; Dan Liu; Ming Lu (Asian Development Bank Institute (ADBI), 2017)
This paper examines the relationship between city size, migration, and urban income inequality using the 1% sample of the 2005 Census in the People's Republic of China (PRC). We calculate various measures of within-city income inequality for 252 PRC cities. It is found that city income inequality is significantly and positively correlated with city population size. As rural-to-urban migration is crucial in determining city size distribution in the PRC, we focus on exploring the role of massive migration into big cities on shaping this size-inequality relationship. We find that the share of migrants alone accounts for more than 40% of the city-size inequality premium. This is mainly because migration leads to a higher skill premium in larger cities by changing the skill composition of the labor force in those places. The main findings still hold after we deal with the endogeneity of migration using an instrument variable approach.
Keywords: R12; O18; J31; 330; city size; income inequality; migration; skill premium; People's Republic of China